Financing Mechanisms for Agro-Climatic Advisory Services and Impact on Productivity and Income of Smallholder Grain Farmers in Northern Ghana: A Gendered Analysis - Odoi, M. E. (University of Ghana, 2024)
This study explores gender-responsive financing mechanisms for Agro-Climatic Advisory Services (ACAS) and their impact on productivity and income among smallholder grain farmers in Northern Ghana. The research addresses four primary issues: (1) the nature of financing mechanisms and their effects on ACAS accessibility, (2) factors influencing ACAS access among male and female farmers, (3) determinants of ACAS adoption by gender, and (4) ACAS's impact on productivity and income. Guided by random utility theory and gender-intersectionality theory, and employing a mixed-methods research design, the study combines quantitative and qualitative approaches for the analysis. Data were collected from 730 smallholder farmers across the Northern and Savannah regions of Ghana using semi-structured questionnaires, interviews, and focus group discussions. Analytical techniques included econometric modeling and descriptive analysis to evaluate factors influencing access, adoption, and outcomes of ACAS. The findings reveal significant disparities in financing mechanisms supporting ACAS. Sources such as grants, loans, and Village Savings and Loan Associations (VSLAs) were identified, with grants being more accessible to male farmers and younger females benefiting more from VSLAs. The study highlights the pivotal role of public-private partnerships in ensuring sustainable ACAS financing. However, systemic barriers limit equitable access, with women and youth disproportionately affected. Key determinants of access include education level, farm size, membership in farmer organizations, and gender. Female farmers face additional constraints due to time poverty, cultural norms, and limited mobility, underscoring the need for gender-sensitive interventions. Regarding ACAS adoption, results show that factors such as trust in information sources, ease of access, and alignment of advisory content with local farming practices significantly influence uptake. Female farmers demonstrated lower adoption rates due to limited financial resources and restricted access to information networks. However, targeted interventions addressing these barriers increased adoption rates, with notable gender-specific impacts. The study finds that adoption of ACAS significantly improved productivity, with Integrated Pest Management (IPM) ACAS achieving the highest gains. Female adopters of IPM recorded an increase of 314.69 kg/hectare in productivity, compared to 283.81 kg/hectare for male adopters. Similarly, Water Management Irrigation (WMI) and Crop Planning Weather Forecast (CPWF) services yielded productivity increases of 309.68 kg/hectare for females and 273.48 kg/hectare for males. The benefits of ACAS adoption were more pronounced among adult farmers, who leveraged greater experience and access to resources. Impacts on income were similarly pronounced. Female adopters of IPM ACAS experienced an income increase of GHS 3866.83 per hectare, while their male counterparts gained GHS 3166.54 per hectare. WMI adopters reported income gains of GHS 3701.41 for females and GHS 1906.96 for males among youth, reflecting the gendered distribution of benefits. CPWF services demonstrated income gains of GHS 3019.55 per hectare for adult females and GHS 2147.84 per hectare for adult males. These results underscore the transformative potential of ACAS in enhancing economic resilience but also highlight persistent gender disparities. In conclusion, the study underscores the transformative potential of ACAS in improving productivity and income among smallholder farmers while highlighting the critical need for gender-responsive financing mechanisms. Addressing disparities in access and adoption requires promoting inclusive policies, expanding education and training, strengthening financial support systems, and fostering public private collaborations. Policy recommendations include integrating ACAS into national agricultural programs, providing targeted subsidies for marginalized groups, and enhancing the institutional capacity to deliver gender-sensitive services. These measures are vital for maximizing the benefits of ACAS and achieving sustainable agricultural development in Northern Ghana.
PhD. Agribusiness
Keywords: Agro-Climatic Advisory Services (ACAS); farmers; Ghana